LEGAL PROTECTION OF HUMAN RIGHTS IN THE STATE ADMINISTRATION PROCESS IN SINGAPORE - Marpaung, Gresnita Br; Sirait, Selly Ani Monica; Sirait, Antha Fabriano (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This research discusses aspects of legal protection of human rights in the context of state administrative processes through a comparative study approach examining the legal systems and cultures between Indonesia and Singapore as two ASEAN member countries with fundamental differences. The focus of the study is directed at identifying differences in administrative law systems, administrative court mechanisms, and procedures for resolving administrative disputes in both countries. This research uses a normative method with analysis of legislation and literature review to reveal differences and similarities in the implementation of state administrative law as part of public law.The study highlights significant differences in the system of government and administrative judiciary institutions, where Indonesia has the State Administrative Court specifically handling administrative disputes, while Singapore resolves such administrative disputes through general courts with a judicial review mechanism. In addition, there are differences in the enforcement of immigration administrative sanctions; Indonesia tends to emphasize aspects of protection and systematic regulation, while Singapore implements sanctions that are repressive in nature with the aim of creating a deterrent effect for violators. These findings make a significant contribution to the development of administrative law and serve as a reference for policy innovation to sustainably improve public welfare